2009
DOI: 10.5585/rai.v6i1.219
|View full text |Cite
|
Sign up to set email alerts
|

The Innovation Process Under the Institutionalist Perspective: An Etnographic Study on Facilities Management in the Automobile Company at Sao Paulo State

Abstract: Palavras-chave: Gestão de facilidades, inovação, teoria institucional.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
4

Year Published

2019
2019
2019
2019

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 9 publications
0
4
0
4
Order By: Relevance
“…Treatment on the one demonstrated in Figure 3 and explained in Table 4 allows to affirm that in the institutionalized environment, the organizations undergo pressures, many times of regulative, culturalcognitive and normative forms, as explicit in Quinello and Nascimento (2009). In this case, such a cognitive scenario allows restoring actions that aim to conserve natural resources, preserving the capacity of the environment.…”
Section: Sourcementioning
confidence: 99%
See 3 more Smart Citations
“…Treatment on the one demonstrated in Figure 3 and explained in Table 4 allows to affirm that in the institutionalized environment, the organizations undergo pressures, many times of regulative, culturalcognitive and normative forms, as explicit in Quinello and Nascimento (2009). In this case, such a cognitive scenario allows restoring actions that aim to conserve natural resources, preserving the capacity of the environment.…”
Section: Sourcementioning
confidence: 99%
“…Thus, it is observed that the more specialized and technical the operations in an organization are, and the more precise the purpose of the organization, the less likely the internal and external agents will negatively affect organizational development. In this way, it is possible to consider that awareness for sustainability implies the institutional diffusion of this concept of value of the organization, adding this to the technical requirements in the task environment, following the prescriptive approach in Quinello and Nascimento (2009). Casagrande and Lavanda (2015) concluded an analysis of the relationship between corporate governance and sustainability, based on the legitimacy and approach of institutional theory.…”
Section: Main Concepts Of Institutionalist Theory Valid For the Instrmentioning
confidence: 99%
See 2 more Smart Citations
“…Para que as inovações tenham sucesso, em ambientes complexos como os organizacionais, devem ser institucionalizadas. Uma vez institucionalizadas, poderão ampliar a vantagem competitiva por meio dos produtos ou serviços gerados, com sustentabilidade e legitimidade perante os beneficiários, diluindo mais rapidamente os altos investimentos que cercam qualquer atividade de desenvolvimento destes produtos ou serviços (QUINELLO;NASCIMENTO, 2009).…”
Section: De Acordo Com Van Deunclassified